Effects of an evidence-based falls risk-reduction program on physical activity and falls efficacy among oldest-old adults - Cho, Jinmyoung; Smith, Matthew Lee; Ahn, SangNam; Kim, Keonyeop; Appiah, Bernard; Ory, Marcia G. (Frontiers in Public Health, 2015)
.